2008
DOI: 10.1111/j.1572-0241.2008.02180.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil as Second Line Therapy in Autoimmune Hepatitis?

Abstract: In the light of its good tolerability, MMF seems to be an alternative for patients who could not tolerate azathioprine previously. However, our data suggest that a majority of patients fail MMF particularly if they are switched because of an insufficient response to azathioprine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(69 citation statements)
references
References 18 publications
4
60
0
3
Order By: Relevance
“…A recent retrospective European study confirms this observation and underlines that mycophenolate mofetil is helpful to overcome azathioprine intolerance rather than resistance [18]. However, larger randomized prospective studies are required to evaluate the efficacy of mycophenolate mofetil in induction and maintenance of remission compared to the standard therapy with azathioprine.…”
Section: Alternative Treatment Strategiesmentioning
confidence: 53%
“…A recent retrospective European study confirms this observation and underlines that mycophenolate mofetil is helpful to overcome azathioprine intolerance rather than resistance [18]. However, larger randomized prospective studies are required to evaluate the efficacy of mycophenolate mofetil in induction and maintenance of remission compared to the standard therapy with azathioprine.…”
Section: Alternative Treatment Strategiesmentioning
confidence: 53%
“…In patients intolerant to azathioprine, mycophenolate mofetil seems to be a relatively good alternative [92][93][94]. It appears to be of very limited efficacy in patients with an insufficient response to azathioprine [95], but experience in children is more favorable than in adults [96]. In these patients stronger immunosuppressive agents appear to be required, and good results have been reported with cyclophosphamide [97], methotrexate [98], cyclosporine [99], tacrolimus [94,100] and infliximab [101].…”
Section: Non-responsementioning
confidence: 96%
“…However, results from a multicentre European study (n = 37) were more sobering, with MMF inducing a biochemical response in only 43% of cases, any benefit largely being restricted to patients intolerant of azathioprine [Hennes et al 2008]. More favourable reports from Greece (n = 59) and the Netherlands (n = 45) found that 67-88% of patients taking MMF as an alternative to azathioprine achieved biochemical remission [Zachou et al 2011;Baven-Pronk et al 2011].…”
Section: Alternative Treatmentsmentioning
confidence: 99%